Pursuing climate resilient coffee in Ethiopia – A critical review. Issue 91 (May 2018) - Hirons, M.; Mehrabi, Z.; Gonfa, T.A.; Morel, A.; Gole, T.W.; McDermott, C.; Boyd, E.; Robinson, E.; Sheleme, D.; Malhi, Y.; Mason, J.; Norris, K.
Abstract: This paper provides a multi-scalar examination of the Ethiopian coffee sector and its pursuit of climate resilience. Concern is growing about the potential impact of climate change on Arabica coffee in Ethiopia and the 25 million livelihoods it supports. Arabica coffee has a relatively narrow envelope of climatic suitability and recent studies suggest that the area of bioclimatically suitable space for the species in its native Ethiopia could decline dramatically in the coming decades. We adopt a critical perspective on resilience that reflects on the situated nature of the ecology/science of coffee and climate change and the operation of social, economic, and discursive power across scales, paying particular attention to the differentiated impacts of climate change and associated resilience strategies. This analysis begins by reviewing Ethiopia's Climate Resilient Green Economy strategy and argues that the current lack of attention to coffee is inappropriate considering the coffee sector's vulnerability to climate change, economic importance and association with forests. The paper then examines the contemporary coffee sector which provides the context for reflecting on three potential responses to the threat climate change poses; a spatial response from farmers, adaptive farm management responses such as changing shade levels and the development of the country's genetic resources to cultivate improved varieties. The analysis explores the disconnect between the interventions emerging from national and international institutions and the local context. The multi-scale approach highlights the presence of complex normative trade-offs associated with pursing climate resilience strategies and reinforces the importance of appreciating the dynamics which influence decision-making in the country.